2003
DOI: 10.1089/108076803321637690
|View full text |Cite
|
Sign up to set email alerts
|

Ganciclovir Release Rates in Vitreous from Different Formulations of 1-O-Hexadecylpropanediol-3-Phospho-Ganciclovir

Abstract: In vitreous, HDP-P-GCV as a crystalline formulation was converted to GCV more rapidly than liposomal formulation of HDP-P-GCV. Vitreous cells may play an important role in the metabolism of either formulation of HDP-P-GCV delivered into vitreous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The dissolved molecules enter the cells and are cleaved intracellularly by phospholipase C into hexadecyloxypropanol and the parent drug. 9 In the present study, we used the same concept and technique to synthesize an ether lipid ester of cyclic cidofovir, HDP-cCDV. Intravitreal injection of 100 g or lower doses of HDP-cCDV crystals provided an ideal drug depot that floated in the inferior vitreous cavity without disturbing the visual axis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dissolved molecules enter the cells and are cleaved intracellularly by phospholipase C into hexadecyloxypropanol and the parent drug. 9 In the present study, we used the same concept and technique to synthesize an ether lipid ester of cyclic cidofovir, HDP-cCDV. Intravitreal injection of 100 g or lower doses of HDP-cCDV crystals provided an ideal drug depot that floated in the inferior vitreous cavity without disturbing the visual axis.…”
Section: Discussionmentioning
confidence: 99%
“…There was little parent drug detectable when prodrug was incubated with a heatinactivated vitreous sample, but conversion was detected readily by native vitreous that contains cells. 9 It has been known that CDV is phosphorylated to cidofovir diphosphate, the active form of cidofovir that has a long intracellular halflife. 13 Indeed, the pretreatment studies indicated at least 100 days of pharmacologic effect against HSV-1 infection of the rabbit retina.…”
Section: Discussionmentioning
confidence: 99%
“…With the current ex vivo infusate, the sample was only subjected to HDP-CDV detection. Based on our previous publication, CDV and various metabolites are possibly present in the infusate and some of metabolites may not be qualified [18, 35]. Therefore, instead of characterizing metabolites in vitro we conducted in vivo efficacy studies to evaluate this drug delivery system.…”
Section: Discussionmentioning
confidence: 99%